Identification of Social Strata through Spoon Class Theory In the Parasite Film - Andhita Ramadhania Pristiawati; Rustono Farady Marta; Hana Panggabean; Kristina Nurhayati; Rizki Briandana (COMMUNICATION MAJOR, 2023)
Film is one of the works that can be used as a medium for communication and the delivery of messages and meanings, both implicit and explicit through an engaging storyline. Along with the development of films, particularly in South Korea, more diversified and excellent films and dramas are being made are. Parasite is a 2019 South Korean film directed by Bong Joon-ho and won the Oscar 2020. This film represents the social gap in the lives of The Kim Ki Taek’s and The Park Dong Ik’s in contemporary South Korea. The Parks are affluent family with a large house and live in upscale housing. The Kim’s, however, are poor family of four who reside in an overcrowded home that resembles a semi-basement. The story begins with Kim Ki Woo, the son of The Kim’s, who joins The Park’s as an English teacher. Eventually, he succeeds in bringing his entire family to work for The Kim’s and conducts a number of frauds and crimes. We are interested in researching this film because of the storyline which describes contemporary living, and the presentation of the clean cinematography. This study aims to look at the identification of social strata in South Korea through spoon class theory through this film by examining the process of nonverbal communication and stereotypes. In this qualitative descriptive study, the social context, text, and social cognition of films are examined using the Teun Van Dijk model of critical discourse analysis to analyse. The data is collected by watching the entire film.Keywords: Nonverbal Communication; South Korean film; Spoon Class Theory; Stereotype; Teun Van Dijk